PENGARUH PENGGUNAAN BUKU KERJA BERBASIS KONTEKSTUAL DALAM PEMBELAJARAN PBI TERHADAP PENCAPAIAN KOMPETENSI IPA FISIKA SISWA KELAS VIII SMPN 3 KECAMATAN PAYAKUMBUH - Karmila Sari (Universitas Negeri Padang, 2014)
The subject matter is abstract Physics lot, so it requires a contextual learning resources, but its availability is limited. One alternative to overcome this problem is the use of contextual based workbook. Type of research is quasi experimental. The population is all students in grade VIII SMPN 3 at Payakumbuh listed in the academic year 2012/2013. Sampling was conducted through cluster random sampling technique. Data taken in the form of student learning outcomes. Data collection techniques used for the cognitive domain is a written test, while for the affective and psychomotor is the observation sheet. Analysis using t-test at the 5 % significance level. The results showed that the learning outcomes in the experimental class increased in both the cognitive, affective and psychomotor. It is believed to be a result of the treatment given, it can be concluded that there are significant contextual usage in a workbook based on the achievement of learning competencies problem based instruction Physical Science class VIII SMPN 3 at Payakumbuh